Applications of Direct Analysis in Real-Time Mass Spectrometry in Traditional Chinese Medicines Analysis - WANG Xing-yu1; GU Wen-yi1; ZHANG Fang-li1; ZHANG Dan1; LI Lin-nan1; WANG Zheng-tao1,2; YANG Li1,2 (Zhipu Xuebao, 2023)
Direct analysis in real-time mass spectrometry (DART-MS) is an emerging in-situ ionization mass spectrometry analysis technology in recent years. DART is a non-contact surface desorption ionization technique, which is based on the principle of using helium or nitrogen as the working gas and generating excited high-energy particles by electric discharge. The excited state particles are accelerated by rapid heating and electric force, which instantly ionize the volatile compounds on the surface of the sample to be measured under atmospheric pressure, and then detected by mass spectrometry, thus achieving real-time direct analysis of the sample. DART-MS has the characteristics of simple sample preparation, quick and in-situ analysis. Since DART-MS was reported in 2005, it has become one of the most broadly used direct analysis methods and is extensively applied for the direct analysis of the quality, safety, origin and characteristics of food samples. Besides, it has been widely used in biomedicine, environmental monitoring, public safety, and drug analysis as well. Traditional Chinese medicines (TCMs) have been used for thousands of years in China, which gradually move towards to the world arena. The composition of TCM is very complicated, often containing many different chemical components of different types and properties, such as flavonoids, alkaloids, terpenoids, etc. Therefore, the analysis of the chemical basis of the efficacy and quality evaluation of TCMs are very crucial. In recent years, the development of DART-MS technology has provided many new opportunities for direct and rapid analysis of active ingredients in TCMs. The review was focused on the applications of DART-MS in TCMs, which covered the principle, characteristics, influencing factors and technological progress of DART-MS technology, and systematically summarized the research and application of this technology in TCMs, including qualitative and quantitative analysis. In addition, this review briefly introduced the progress of the application of DART-MS in combination with other techniques, such as thin-layer chromatography, imaging mass spectrometry and solid-phase microextraction in the profiling of TCMs, and provided further perspectives on its application development.